Genetic association study of tumour necrosis factor polymorphisms in chronic rhinosinusitis with and without nasal polyps - Misron, Khairunnisak (2016)
Chronic rhinosinusitis (CRS) is a chronic inflammatory condition which initiates the cascade of inflammatory responses resulting in production of various proinflammatory cytokines. TNF is one of the proinflammatory cytokines that has crucial role in the pathogenesis of CRS. This case-controlled study aimed to identify the presence and associations of TNFα -1031 and TNFβ +252 gene polymorphisms between CRS and healthy controls as well as between CRSwNP and CRSsNP. Another purpose of this study was to investigate the associations of these genes polymorphisms with factors related to CRS. Forty eight CRS participants which comprised of 24 CRSsNP and 24 CRSwNP participants together with 48 healthy controls were enrolled in this study. All DNA samples were collected from buccal mucosa and subsequently, genotyped for TNFα -1031 and TNFβ +252 genes by mean of polymerase chain reaction (PCR) and restriction fragment length polymorphisms (RFLP). The statistical analysis were carried out using Chi-square Test or Fisher’s exact test and multiple logistic regression to determine the associations of TNFα -1031 and TNFβ +252 gene polymorphisms in CRS with and without nasal polyps and risks of CRS. Our findings confirmed the presence of TNFα -1031 gene polymorphisms in which the homozygous wild-type (TT) and heterozygous mutant-type (TC) wereevenly distributed between CRS and healthy controls as well as in CRSsNP and CRSwNP. Homozygous mutant-type (CC) was absent in our population. Similarly, the wild-type allele (T) and mutant allele (C) revealed balance distributions. As for TNFβ +252 gene polymorphisms, the heterozygous mutant-type (AG) was identified to be more prevalent in comparison to homozygous wild-type (AA) and homozygous mutant-type (GG). The wild-type allele (A) and mutant-type allele (G) distributed uniformly. Statistical analysis of genotype and allele frequencies of TNFα -1031 and TNFβ +252 gene did not show any significant associations between CRS and healthy controls as well as between CRSwNP and CRSsNP. However, a significantly statistical difference of TNFα -1031 was observed in CRS participants with atopy (pvalue = 0.037) but not asthma and ASA intolerance. There were no significant associations of TNFβ +252 gene polymorphisms with factors related to CRS. In conclusion, the presence of TNFα -1031 and TNFβ +252 gene polymorphisms in current study did not render any significant associations between CRS and control as well as CRSsNP and CRSwNP. However, this study suggests that the presence of TNFα -1031 gene polymorphisms in CRS patients with atopy may be associated with increase susceptibility towards CRS.